Development of the youth athlete - Armstrong, Neil (Abingdon, Oxon New York, NY Routledge, 2019)
Development of the Youth Athlete offers a single-authored, well-illustrated, evidence-based, and integrated analysis of the development and trainability of the morphological and physiological characteristics which influence sport performance in youth. The book critically analyses the development of the youth athlete in the context of current and future sport performance and long-term health and well-being. Development of the Youth Athlete identifies the principal controversies in youth sport and addresses them through sport-specific examples. Presenting a rigorous assessment and interpretation of scientific data with an emphasis on underlying physiological mechanisms, the book focuses on the interactions between growth, maturation, and: sport-related fitness; sport-specific trainability; sport performance; challenges in youth sport. Providing up-to-date, coherent critical discourse on youth athlete development currently available, Development of the Youth Athlete is essential reading for students, lecturers, sport medicine practitioners, researchers, scholars, and senior coaches with an interest in youth sport, exercise science, and sport medicine
Growth, maturation, and youth sport -- Exercise metabolism and youth sport -- Hormones, energy, nutrition, and youth sport -- Growth, maturation, and youth athletes -- Youth sport-related motor performance -- Muscle strength -- High-intensity exercise -- Maximal and peak oxygen uptake -- Submaximal indicators of aerobic fitness and sport performance -- Pulmonary oxygen uptake kinetics.
Includes bibliographical references and index
Keywords: Child athletes; Physical fitness for youth; Sports for children; Exercise -- Physiological aspects